Frontline healthcare workers experiences and challenges with in-person and remote work during the COVID-19 pandemic: A qualitative study - Sims, Holly; Alvarez, Carmen; Grant, Kimesha; Walczak, Jessica; Cooper, Lisa A.; Ibe, Chidinma A. (Frontiers in Public Health, 2022)
Introduction: The COVID-19 pandemic created new and exacerbated existing stressors for frontline healthcare workers. Despite being disproportionately affected by COVID-19, little is known about the experiences of frontline healthcare workers serving marginalized populations in community settings. Design: We used qualitative descriptive methods to understand the experiences of 12 frontline healthcare workers (HCW) supporting primarily underserved populations in outpatient settings during COVID-19. Interviews were conducted from March – April 2021. Methods: Interviews were held virtually via Zoom using a semi-structured interview guide. Interviews were audio-recorded, transcribed verbatim, and uploaded into NVivo 12 qualitative data analysis software. The transcripts were dually coded by members of the research team and a thematic analysis was conducted. Results: Four major themes from the interviews were identified: stressors and burnout, coping strategies, organizational support, and recommendations. HCWs described how the early adjustment period to the pandemic created new challenges as they attempted to navigate changes in the workplace and altered responsibilities at home. HCWs felt largely unsupported by their organizations as they attempted to cope with stressors. Organizational support programs and resources often did not meet frontline workers’ needs, and sentiments of unappreciation from leadership contributed to feelings of burnout and frustration as pandemic-related challenges persisted and evolved. Conclusion: Despite encountering numerous stressors at work and home, resulting from pandemic-related disruptions, frontline HCWs continued to provide care for their clients while navigating emerging challenges. Health organizations should include HCWs in decision-making processes when implementing support systems for workers during times of crisis.